Comparative Study of Biology Student Learning Achievement with Cooperative Model by Numbered Head Together (NHT) and Talking Stick in Class XI SMA Pembangunan Laboratorium UNP - Dhea Delara Iryanda; Dezi Handayani; Helendra Helendra (Bioeducation Journal, 2017)
This research purpose to comparestudents’biology learning achievement that used cooperative learning model Numbered Head Together with the other class that usedTalking Stickinclass XI at SMA PembangunanLaboratoriumUniversitasNegeri Padang. This research was based on the problem in this school that still dominated by teacher centered learning and low interest and activityof students in learning, those make the students bored in the classroom. This research was quasi-experimental research which used the static group comparison designthat modified, because in this research didnot used any control class. Sample of this research was choosen by saturation sampling. Result showed thatstudents’ biology learning achievementusing Numbered Head Togetherhas significant difference with using Talking Stick learning model.